The Clinicopathologic Features, Survival Rate and Prognostic Factors on Survival of Patients with Stomach Cancer - Chancharoen , Alongkorn (Srinagarind Medical Journal, 2022)
Background and Objectives: Every year, a large number of people worldwide suffer from gastric cancer and die from stomach cancer. The objective of the study was to explore the clinicopathological characteristics, survival rate, and prognostic factors of stomach cancer patients. Methods: These was a retrospective cohort study, all data were collected from medical record of patients with stomach cancer at Roi Et hospitals between January 1, 2015 and December 31, 2020, and were follow-up for the final vital status or end of the study period on April 30, 2022. Data analysis used descriptive statistics, The Kaplan-Meier survival curve , Log rank test, and Cox proportional hazard model. The statistical significance was set at p<0.05. Results: Of 354 patients, most of them were male 61.58%, mean age of 59.76± 13.35 years , cancer Stage IV 53.95%, and H. pylori infection 62.15%. The total follow-up times were 4,898 person-months. Of 308 cases died at the end of the study with an incidence rate of 6.28 per 100 person-months. The overall median survival time was 5.30 months. The 1, 3, and 5 years survival were 31.92%, 13.29%, and 10.85% respectively. The prognosis factors on survival of patient were cancer stage IV (Adj HR.: 3.22; 95% CI; 1.57-6.60), direct extension (Adj HR.: 2.43; 95% CI; 1.43-4.12), cancer metastasis to lung / pleura (Adj HR.: 2.67; 95% CI; 1.17-6.08), peritoneum (Adj HR.: 2.04; 95% CI; 1.03-4.04), bone (Adj HR.: 3.16; 95% CI; 1.99-10.06), brain (Adj HR.: 12.73; 95% CI; 1.69-95.55), lymph node (Adj HR.: 1.92; 95% CI; 1.04-3.54), multiple sites (Adj.HR: 2.11; 95% CI; 1.54-2.88), H. pylori infection (Adj.HR: 3.63 (2.79-4.74), and supportive treatment (Adj HR.: 2.45; 95% CI; 1.93-3.10) Conclusion: This study revealed that survival of stomach cancer patient associated with advanced stage of diseases, H. pylori infection, metastasis of the cancer to other organs and supportive treatment. Early detection and diagnosis, and accessing effective treatments at the right time were essential factors that increased survival of patients.